Kepuasan Finansial pada Individu Menikah di Kota Surabaya - Sholihah, Avikhatus (Jurnal Ilmu Manajemen, 2021)
Married people have more needs than unmarried people, so they must manage their finances properly to achieve financial satisfaction. If married people can not manage their finance, they will felt dissatisfied with their financial condition. This situation can lead them to divorce by the economic problem. For this reason, this study aims to examine the factors that increase financial satisfaction in married people. Personal income, financial literacy, financial attitude, and financial management behavior will be examined in this study. A total of 110 married people in Surabaya with personal income and age range from 25-65 years were made into a sample in this study. This study uses multiple linear regression by using SPSS 25 program. This study found that personal income, financial attitude, and financial management behavior significantly affect financial satisfaction. While financial literacy does not affect financial satisfaction.